The Effectifeness of Religious Image Stories Teaching Materials on the Learning achievement of Students’s Class 1 SD Negeri 31 Pusuea - Marliana Marliana (Journal of Teaching and Education, 2022)
This study aimed to determine the effectiveness of religiously charged pictorial story teaching materials on learning achievement. The subject of this research was the 1st-grade students of SD Neg. 31 Pusuea with a total of 14 students. The teaching material used is a picture book containing religious values. This study used experimental research methods with the research design used as pre-experiment one group pre-test-posttest. The test questions were in the form of multiple choices with a total of 20 questions. Data analysis used Normalized Gain Test. The results showed that the total pretest score of all students was 1890 and the total post-test score of all students was 2480. These results were processed using the N-Gain formula and reached a value of 0.53 with the interpretation of "Medium", with these results there was a significant increase in student achievement by using illustrated story teaching materials with religious values. It can be concluded that teaching materials containing religious values are effective on student achievement in grade 1 SD Neg. 31 Pusuea.